Intertemporal price discrimination in storable goods markets - Igal Hendel; Aviv Nevo (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2011)
We study intertemporal price discrimination when consumers can store for future consumption needs. To make the problem tractable we offer a simple model of demand dynamics, which we estimate using market level data. Optimal pricing involves temporary price reductions that enable sellers to discriminate between price sensitive consumers, who anticipate future needs, and less price-sensitive consumers. We empirically quantify the impact of intertemporal price discrimination on profits and welfare. We find that sales: (1) capture 25-30% of the profit gap between non-discriminatory and third degree price discrimination profits, and (2) increase total welfare.
Keywords: 330; Konsumentenverhalten; Rohstoffversorgung; Preisdifferenzierung; Wohlfahrtsanalyse; USA